Mudanças climáticas e cartografia socioambiental: um estudo no município de Fernandópolis - SP - (:unkn) unknown (Universidade Brasil, 2024)
Climate change represents a growing challenge both locally and globally, directly and indirectly affecting ecosystems, economies, and societies in various regions of the planet. The increase in global average temperature, the intensification of extreme weather events, and the alteration of precipitation patterns are some of the effects already observed, which have profound consequences for biodiversity, agriculture, water resources, and public health. In this scenario, the implementation of educational strategies aimed at raising awareness among future generations about environmental impacts and ways to mitigate and adapt to these changes becomes essential. The research aimed to understand the characteristics of climate change, the development of socio-environmental cartography for the municipality of Fernandópolis/SP, and the creation of a didactic booklet that includes such content. The work seeks to contribute to the dissemination of relevant information, focusing on the education of children up to 10 years old in elementary school, aiming to promote environmental education and awareness. It was developed through a qualitative approach, with bibliographic research from various sources, both primary and secondary, such as books, scientific articles, theses, dissertations, and legal documents from environmental and governmental organizations. The search was conducted in academic databases such as Scielo, Google Scholar, and institutional repositories, and the selection of references was guided by criteria of relevance, timeliness, and scientific quality. It can be concluded that the municipality of Fernandópolis/SP stands out for implementing interdepartmental programs and projects aimed at improving environmental and quality of-life indices. The creation of the environmental booklet contributes to the expansion of the availability of didactic materials on the themes and enables training for environmental awareness and preservation, integrating the content into the local reality.
Keywords: Educação ambiental; Materiais didáticos; Cartilha ambiental; Conscientização ambiental; Cartografia - Fernandópolis; Mudanças climáticas - Fernandópolis; Legislação Ambiental